Virtual Communication Across Differences: Development of a Workshop on Managing Patient Bias. (11th October 2022) - Zewdie, Monica; Duval, Margaret; Liu, Chang; Bachman, Sharon L.; Moore, L. Gordon; Mohess, Denise; Kapadia, Muneera R.; Dort, Jonathan; Newcomb, Anna B.
Abstract : Problem: Despite the prevalence and detrimental effects of racial discrimination in American society and its health care systems, few medical schools have designed and implemented curricula to prepare medical students to respond to patient bias and racism. Approach: During the summer of 2020, a virtual communication class was designed that focused on training medical students in how to respond to patient bias and racism. Following brief didactics at the start of the session, students practiced scenarios with actors in small groups and received direct feedback from faculty. For each scenario, students were instructed to briefly gather a patient's history and schedule an appointment with the attending whose name triggered the patient to request an "American" provider. In one scenario, the patient's request was motivated by untreated hearing loss and difficulty understanding accents. In another, it was motivated by racist views toward foreign physicians. Students were to use motivational interviewing (MI) to uncover the reasoning behind the request and respond appropriately. Students assessed their presession and postsession confidence on 5 learning objectives that reflect successful communication modeled after MI techniques. Outcomes: Following the session, student skills confidence increased in exploring intentions and beliefs ( P = .026), navigating a conversation with a patient exhibiting bias ( P = .019) and using nonverbal skills to demonstrate empathy ( P = .031). Several students noted that this was their first exposure to the topic in a medical school course and first opportunity to practice these skills under supervision. Next Steps: The experience designing and implementing this module preparing students in responding to patient bias and racism suggests that such an effort is feasible, affordable, and effective. With the clear need for such a program and positive impact on student confidence navigating these discussions, including such training in medical school programs appears feasible and is strongly encouraged.